Inter-Rater Reliability Regarding the Radiolucencies Associated with the Second Molar Adjacent an Impacted Third Mandibular Molar - Muhammad Taha Qamar; Mariah Muhammad Ashraf; Bakhtawar Zahid; Amina Nawaz; Abraiz Azhar; Darab Fatima Babry (Gandhara University, 2023)
OBJECTIVES To assess the inter-rater reliability regarding the radiolucencies associated with a second molar adjacent to an impacted third molar. METHODOLOGY A cross-sectional comparative study was conducted in the College of Dentistry, Sharif Medical and Dental College, Lahore, in which dentists from four different specialities, namely; Oral Pathology, Endodontics, Prosthodontics and Oral and Maxillofacial surgery, were included as raters. 21 Orthopantomograms were assigned to each rater for assessing radiolucencies associated with a second molar adjacent to an impacted third molar. RESULTS The level of agreement regarding the radiolucencies associated with the second molar observed on the Orthopantomograms between rater 1 with rater 2 (κ=0.158., p=0.036) and rater 1 with rater 3 (κ=0.139, p=1.000) was very weak but was fair between rater1 and 4 (κ=0.271, p=0.200). CONCLUSION The only radiolucency that rater one observed was external root resorption. Rater 2 identified one case of radiolucency as dental caries and another as caries and periapical radiolucency that were identified by Rater 1 as external resorption; hence they had a weak agreement between Rater 1 and Rater 2 regarding the radiolucencies associated with second molars. Rater 3 identified radiolucencies owing to caries which were reported to be radiolucency due to external resorption by rater 1, and this agreement was weak. Most radiolucencies determined by rater 1 as external resorption were reported to be external resorption by rater 4, resulting in a fair agreement between rater 1 and 4.